Elizabeth J. Perry y Christine Wong, (eds.), The Political Economy of Reform in Post-Mao China, Cambridge, Mass., The Council on East Asian Studies, Harvard Universitary Press, 1985, 331 pp. - Connelly, Marisela (El Colegio de México, 1987)
Dwight H. Perkins, China, Asia's Next Economic Gigant?, Seattle, University of Washington Press, 1986, 98 pp.